Performance, Methane Emission, Nutrient Utilization, and the Nitrate Toxicity of Ruminants with Dietary Nitrate Addition: A Meta-analysis from In Vivo Trials - M. Abdelbagi; R. Ridwan; A. Fitri; Nahrowi; A. Jayanegara (Faculty of Animal Science, Bogor Agricultural University, 2023)
This study aims to evaluate the effects of dietary nitrate addition on performance, methane emission, nutrient utilization, and the nitrate toxicity of ruminants by using the meta-analysis methodology from in vivo trials. A total of 38 published papers and 139 studies were used. Parameters observed were feed intake, animal performance, enteric methane emission, and nitrate toxicity. Data were subjected to the mixed model methodology. Nitrate doses or forms were treated as fixed factors, while the different studies were treated as random factors. Results revealed that nitrate supplementation significantly decreased the milk protein content, milk fat content, dry matter intake, gross energy intake, the molar proportion of the propionic acid, methane production, and the metabolism of vitamin A in a linear pattern (p<0.05). Moreover, nitrate addition significantly increased nitrate intake, the molar proportion of the acetic acid, the ratio of acetic acid to propionic acid, hydrogen molecule production, microbial protein synthesis, and nitrite blood levels (p<0.05). However, treatments did not affect the milk yield, final body weight, nitrate retention, and blood methemoglobin. There was a significant interaction among the animal types and the nitrate (forms and doses) on the milk protein content, dry matter intake, rumen pH value, total volatile fatty acids, the molar proportion of propionic acid, NH3 concentration, H2 molecule, microbial protein synthesis, metabolism of vitamin A, and the blood methemoglobin. This concludes that nitrate supplementation is an alternative feed additive for mitigating the enteric methane in ruminants without any adverse effects on animals’ health or performance despite its impact on the feed consumption rate.